Охорона рослин in situ та ex situ в Україні - Melnyk, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Ukraine is characterized by high diversity of wild flora. Flora of Ukraine is one of the richest in Europe and includes 4523 species of vascular plants. Ukraine occupies 5.7 % of area of Europe and it contains 37 % of European vascular plants. 9 % of species of vascular plants of Ukraine are endemics. There are 611 species of vascular plants in the Red Data Book of Ukraine. The nature reserves funds of Ukraine included around 7790 objects, occuping around 5.7 % territory of Ukraine. Now Ukraine has a good perspective for improving the net of protected areas. All botanical gardens in Ukraine are involved in ex situ conservation of plants. The collection of rare and endangered species in M.M. Gryshko National Botanical Garden of National Academy of Sciences of Ukraine harbors 136 species included in Red Data Book. Modeling of the populations of rare and endangered species in artificial forest and steppe communities is an original method of ex situ plant conservation.